Incorporating science communication and bicultural knowledge in teaching a blended volcanology course - B. Kennedy; K. Engel; J. Davidson; S. Tapuke; D. Hikuroa; T. Martin; P. Zaka (Geoscience Communication)
A variety of skills can be taught alongside course content. In the University of Canterbury third-year course on magmatic systems and volcanology, we chose to focus on teaching bicultural competence and science communication, while transforming the course to a more skill-based, flexible, flipped-classroom model. We document the development process and measure student perceptions associated with these skills. We used two edX massive open online courses (MOOCs) on volcanology as skill-focused learning resources to replace lectures and supplement hands-on laboratory and tutorial sessions to teach volcanology.